“Dressed like boys, hair trimmed, a nalla kutti otherwise”: construction of queer suicide in Indian online news media - Jetubhai, Khuman Bhagirath (Frontiers in Sociology, 2024)
Suicide is a significant newsworthy event, and the media often cover cases involving queer individuals. However, there is a notable lack of research on the quality of reporting of queer suicide cases within the Indian context. This article aims to address the existing gap in Indian online news media by investigating the portrayal of queer suicide via content analysis. Content analysis involves qualitatively condensing and interpreting data to extract key consistencies and meanings from a plethora of qualitative material. The newspapers considered span from 2005 to 2022, with data collection conducted in 2023. The author alone identified news articles on queer suicide and conducted the subsequent content analysis. The study reveals that reporting on queer suicide tends to divide queer couples into the gender binary and describes what it deems to be careless sexual conduct driven by obsessive queer love, which, in turn, is blamed for the suicide. Moreover, these reports often do the following: feature families who refuse to accept their children’s identities, adopt dread-filled tones, and cite experts who provide incorrect information while engaging in victim blaming. As a result, the quality of queer suicide reporting in Indian newspapers is deemed substandard and offensive. To address this issue, the study proposes the need for training and curriculum updates in journalistic courses. This way, reporters can develop the skills necessary to sensitively and respectfully report on queer individuals in general and on queer suicide in particular.